1996
DOI: 10.1177/039139889601900406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ELAD Liver Support on Plasma HGF and TGF–β1 in Acute Liver Failure

Abstract: The aim of this study was to investigate the effects of treatment with the extracorporeal liver assist device (ELAD) in patients with acute liver failure (ALF) on plasma hepatocyte growth factor (HGF), the most potent growth factor, and transforming growth factor-beta 1 (TGF-beta 1), an inhibitory factor for liver regeneration. Initial plasma HGF, measured by ELISA, was significantly increased in the ALF patients (7.86 +/- SEM 1.76 ng/ml) compared with normal subjects (0.10 +/- 0.02 ng/ml, p < 0.001). After 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…(15) reported that the addition of selective filter membranes, which have similar sieving coefficients to EC‐4A, to the PE circuit expedited liver regeneration and improved survival time in pigs with fulminant hepatic failure. We have attempted to detect the HGF changes after PE; however, it has previously been noted that an injection of heparin to patients induced an immediate rise of serum HGF and interfered with HGF detection (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…(15) reported that the addition of selective filter membranes, which have similar sieving coefficients to EC‐4A, to the PE circuit expedited liver regeneration and improved survival time in pigs with fulminant hepatic failure. We have attempted to detect the HGF changes after PE; however, it has previously been noted that an injection of heparin to patients induced an immediate rise of serum HGF and interfered with HGF detection (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is some evidence relating to the harmful substances found in the blood in these circumstances, it is not clear how they act, or if filtering them out has any detrimental effect. Indeed some may be required to stimulate hepatic regeneration and the effect of these systems on hepatic regeneration has yet to be fully assessed 100,101 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed some may be required to stimulate hepatic regeneration and the effect of these systems on hepatic regeneration has yet to be fully assessed. 100,101 The literature is difficult to interpret due to the differences in end-points used for different models (i.e. improvement in hepatic encephalopathy, survival after hepatic coma or successful bridging to transplant).…”
Section: Discussionmentioning
confidence: 99%
“…The value of continuous BAL application over several days has also been questioned. Such continuous application may be detrimental to patient outcomes via the removal of important stimulators of hepatic regeneration such as Hepatocyte growth factor (34). Significantly the HepatAssist ® BAL has employed an intermittent 6 h application schedule to help overcome this potential problem and the logistical issues associated with continuous application.…”
Section: Discussionmentioning
confidence: 99%